Um estudo de equações algébricas de 1° grau com o auxílio do software Aplusix - Daniel, José Anisio (2007)
This work is a piece of diagnostic research of the qualitative predominance with the aim of identify the errors and analyze the procedure and strategies that students of 8th grade of Primary Education use to solve algebraic equation of 1st degree. We have used the Software Aplusix as a support tool used for the teaching and learning of algebra. This work is based on a work of Cortes & Kavafian (1999), which shows categories of errors and analyses of strategies used for a group of students of Primary Education from France, in the resolution of algebraic equation of 1st degree. We have worked with eight students of 8th grade of Primary Education of a public school in the interior of Sao Paulo using as a tool of teaching and learning only the Software Aplusix. Using the videotape of Aplusix we identify and analyze the more common errors found in the students exercises. Comparing the results of the pre-test and the post-test we have noticed important advances such as: the right application of distributive property of multiplication in relation to addition and least common multiple, addition of relative numbers, exchange of sign when a term is transferred of a member to another of equality of equation, and others. The equivalence or not among successive stages of equation showed by the software, allowed the student to be constantly asking questions about their errors and strategies of resolution. We have also noticed that the concepts of equivalence and inverse operation were the main causes of errors in the resolution of students exercises and these errors persist in the post-test. This study tries to show ways for new approaches about teaching and learning of algebra equations of the 1st degree Primary Education